Strategy PT. Bank Sumut Syariah Panyabungan Branch Office In Improving The Quality Of Mobile Banking Services - Windari, Windari; Batubara, Sarmiana; Sari, Heny Purnama (Journal of Islamic Financial Technology, 2022)
The role of technology in the development and provision of new products is very important in this competition, therefore Bank SUMUT Syariah launched Mobile Banking or SUMUT Mobile service products. In response to this, Bank SUMUT Syariah strives to improve and maintain the quality of services provided to attract customers. The problem in this research is how the strategy of SUMUT Syariah bank in improving the Quality of Mobile Banking Services. The purpose of this study was to determine how the strategy of Bank SUMUT Syariah in improving the quality of mobile banking services. This research is a type of descriptive qualitative research with interview techniques , documentation and literature study, data processing techniques data examination, data reconstruction and data systematization.The results of the research carried out are Strategies in improving the Quality of Mobile Banking Services. The Bank presents various offers such as a gift program to the public who become customers at PT. Bank SUMUT Syariah Panyabungan branch office. The challenge for Bank SUMUT Syariah is the assumptions/thoughts of ordinary people who are afraid of losing their balance when using the Mobile Banking application and the solution provided by the Bank is by providing education to customers who come to Bank SUMUT Syariah.Keywords: Strategy, Service Quality, and Mobile BankingThe role of technology in the development and provision of new products is very important in this competition, therefore Bank SUMUT Syariah launched Mobile Banking or SUMUT Mobile service products. In response to this, Bank SUMUT Syariah strives to improve and maintain the quality of services provided to attract customers. The problem in this research is how the strategy of SUMUT Syariah bank in improving the Quality of Mobile Banking Services. The purpose of this study was to determine how the strategy of Bank SUMUT Syariah in improving the quality of mobile banking services. This research is a type of descriptive qualitative research with interview techniques , documentation and literature study, data processing techniques data examination, data reconstruction and data systematization.The results of the research carried out are Strategies in improving the Quality of Mobile Banking Services. The Bank presents various offers such as a gift program to the public who become customers at PT. Bank SUMUT Syariah Panyabungan branch office. The challenge for Bank SUMUT Syariah is the assumptions/thoughts of ordinary people who are afraid of losing their balance when using the Mobile Banking application and the solution provided by the Bank is by providing education to customers who come to Bank SUMUT Syariah.Keywords: Strategy, Service Quality, and Mobile Banking